2021
DOI: 10.1159/000520261
|View full text |Cite
|
Sign up to set email alerts
|

Solutions and Gels Containing a Sugarcane-Derived Cystatin (CaneCPI-5) Reduce Enamel and Dentin Erosion in vitro

Abstract: The effect of solutions and gels containing a sugarcane-derived cystatin (CaneCPI-5) on the protection against enamel and dentin erosion in vitro was evaluated. Bovine enamel and dentin specimens were divided into two groups (n=135 and 153/group for enamel and dentin, respectively) that were treated with solutions or chitosan gels containing 0.1 or 0.25 mg/ml CaneCPI-5. The positive controls for solutions and gels were Elmex Erosion Protection™ solution and NaF gel (12,300 ppm F), respectively. Deionized water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…CaneCPI-5 is a novel synthesised sugarcane cystatin [ 121 ]. It strongly binds to hydroxyapatite of the enamel surface and forms a protective layer [ 121 , 122 ]. The CaneCPI-5 can also improve the protective effect of the salivary pellicle by increasing the number of acid-resistant proteins such as cystatin B [ 121 , 123 , 124 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…CaneCPI-5 is a novel synthesised sugarcane cystatin [ 121 ]. It strongly binds to hydroxyapatite of the enamel surface and forms a protective layer [ 121 , 122 ]. The CaneCPI-5 can also improve the protective effect of the salivary pellicle by increasing the number of acid-resistant proteins such as cystatin B [ 121 , 123 , 124 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
“…The CaneCPI-5 can also improve the protective effect of the salivary pellicle by increasing the number of acid-resistant proteins such as cystatin B [ 121 , 123 , 124 ]. In addition, CaneCPI-5 inhibits MMPs and reduces the severity of dentine erosion [ 122 , 123 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Cane CPI-5 has shown promising results in preventing erosive wear (enamel and dentin) in vitro [30,31] and in situ at a concentration of 0.1 mg/ml [32]. Regarding the prevention of enamel caries, a recent study also under microcosm bio lm showed that different concentrations of Cane CPI-5 (0.05, 0.1 and 0.5 mg/ml) were effective in signi cantly reducing the integrated mineral loss when compared to the negative control (PBS) [17].…”
Section: Discussionmentioning
confidence: 99%
“…The immobilization of proteins in the acquired pellicle has been proposed as a new measure for the prevention of ETW [Santiago et al, 2017;Carvalho et al, 2020;Martini et al, 2020;Taira et al, 2020;Frazão Câmara et al, 2021;Pelá et al, 2021a;Pelá et al, 2021b;Santos et al, 2021;Reis et al, 2023]. Among the poten-Fig.…”
Section: Discussionmentioning
confidence: 99%